The Relationship of Physical Activity and Sleep Quality Toward Hypertension Prevalence in Sumberngepoh Village, Malang, Indonesia: English - Jayanata, M. Gita; Fauziah Adhima; Khansa Talitha Rafif; Ludy Diana Wiradhika; Muhamad Bagus Wira; Ramidha Syaharani; Sarah Nia; Khulbizzabidi; Samsriyaningsih Handayani (Universitas Airlangga, 2023)
Hypertension is the highest among non-communicable diseases in Indonesia and the world, with prevalence showing an increase yearly. One of the determinants is having health-risk behaviors such as low levels of physical activity and sleep quality. These risk factors also have a relationship with hypertension in rural areas. This study aims to find the relationship between physical activity, poor sleep quality, and the prevalence of hypertension in Sumberngepoh, Lawang, Malang, Indonesia. This was a case-control study involving a population of Sumberngepoh Village residents older than 18 years old. The assessment of physical activity was measured using the Indonesian Ministry of Health's PTM cohort study questionnaire. The sleep quality was measured using the IFLS-5 questionnaire. Data analysis was performed using SPSS version 27 with univariate analysis using the Chi-square test with a significance value of <0.05. If the expected value was <5, Fisher's exact test was used. logistic regression test was employed for the multivariate analysis. The level of physical activity was significantly related to hypertension (p<0.05). However, the sleep quality was not significantly related to hypertension (p>0.05). Multivariate analysis showed that the level of physical activity was significantly related to hypertension, with an odds ratio of moderate to strenuous physical activity of 0.134. The prevalence of hypertension was significantly related to the level of physical activity in the age group more than 18 years old in Sumberngepoh, Lawang, Malang, Indonesia.